2009
DOI: 10.1038/emboj.2009.170
|View full text |Cite
|
Sign up to set email alerts
|

Far-red light inhibits germination through DELLA-dependent stimulation of ABA synthesis and ABI3 activity

Abstract: Under the canopy, far-red (FR) light represses seed germination by inactivating phytochrome photoreceptors. This elicits a decrease in gibberellins (GA) levels and an increase in abscisic acid (ABA) levels. GA promotes germination by enhancing the proteasome-mediated destruction of DELLA repressors. ABA prevents germination by stimulating the expression of ABI repressors. How phytochromes elicit changes in hormone levels or how GA-and ABA-dependent signals are coordinated to repress germination remains poorly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
146
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(153 citation statements)
references
References 40 publications
6
146
0
1
Order By: Relevance
“…1 G and I, and 2 A and B). RGA enhances RGL2 function and they are both known to stimulate ABA biosynthesis (50), but it remains to be established whether this is through a direct effect on ABA1 expression. We propose that the low germination rates of spt mutant Ler seeds (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 G and I, and 2 A and B). RGA enhances RGL2 function and they are both known to stimulate ABA biosynthesis (50), but it remains to be established whether this is through a direct effect on ABA1 expression. We propose that the low germination rates of spt mutant Ler seeds (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The ABA insensitivity and tolerance to paclobutrazol of ZFP3ox lines could be influenced by reduced transcription of the DELLA factor RGL2 in ZFP3ox seedlings, which is a negative regulator of GA responses (Lee et al, 2002;Tyler et al, 2004). RGL2 was shown to control germination by enhancing ABA-dependent ABI3 and ABI5 activities, which act as final repressors of germination (Piskurewicz et al, 2008(Piskurewicz et al, , 2009. Although the transcript levels of ABI5 and RGL2 were lower in ZFP3ox seedlings, they are probably not direct targets of ZFP3, as their expression was not altered by ZFP3 overexpression after short-term ABA induction (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Mutants deficient in ABA synthesis or signaling in general show reduced dormancy, often accompanied by defects in the seed maturation program, such as reduced reserve accumulation and desiccation tolerance (Nambara et al, 1994). In seeds, the action of ABA is antagonized by that of gibberellin (GA), and numerous studies have shown that an intricate web of crossregulation between ABA and GA levels lies at the heart of the control of seed germination (Seo et al, 2006;Piskurewicz et al, 2008Piskurewicz et al, , 2009. Environmental signals that influence dormancy or germination have been shown to result in the transcriptional regulation of GA and ABA metabolism in the imbibed seed.…”
Section: Introductionmentioning
confidence: 99%